MODEL DISCOVERY LEARNING BERBANTUAN MULTIMEDIA INTERAKTIF UNTUK MENINGKATKAN PENGUASAAN KONSEP DAN KEMAMPUAN PEMECAHAN MASALAH KONSEP FLUIDA DINAMIS - Khumairah; Adiandri Suhaili (GoAcademica Research dan Publishing, 2022)
The purpose of this study was to determine the effect of interactive multimedia-assisted discovery learning models to improve conceptual mastery and problem-solving skills of dynamic fluid concepts for students of SMAN 4 Praya in the 2017/2018 academic year. The research design used was pretest-post test control group design. The population in the study were all students of class XI SMAN 4 Praya totaling 8 classes, while the sample used was 2 classes. Namely class XI MIPA 1 as the experimental class and class XI MIPA 4 as the control class. Data collection techniques used two types of tests, namely multiple choice and essay tests. The hypothesis test of this research was carried out using the MANOVA test. The results showed that there were differences in the ability to master concepts and solve physics problems between groups of students who were taught using the multimedia-assisted discovery learning model and groups of students who did not use the multimedia-assisted discovery model.